RESONANSI PADA RANGKAIAN RLC - LIZELWATI, NOVIA (Sainstek : Jurnal Sains dan Teknologi, 2011)
In an ac circuit containing inductance L, resistance R, and capacitance C, when Xc=XL , the applied voltage V and the current I are in phase, this effect is called resonance. To RLC series ac circuit resonant frequency is got when the value of electric current maximum and minimum to RLC parallel ac circuit. The result an exsperiment, in RLC series ac circuit by using R = 99,5 ohm and R= 32,136 ohm have frequence resonance 1800 Hz, and 1950 Hz for R = 9,185 ohm.Whereas in RLC parallel ac circuit with R = 99,5 ohm have frequence resonance 2000 Hz, and have range 1800 ? 1900 Hz to R= 32,136 ohm,if R = 9,185 ohm frequence resonance 1800 Hz. The value frequence resonance by using formula on theory is 1808,53 Hz. So can get conslusion that the difference of value frequence resonance in exsperiment not significant with theory.Key words: eksperiment of phisic, RLC series ac circuit, RLC parallel ac circuit, resonant frequency